(untitled) (Research, Society and Development, 2021)
The current model used in science education has been criticized for pointing out the need to renew the learning concepts of teachers and students; where the student is a key part of the teaching and learning process. The use of multimedia, computer games and access to the Internet become fundamental devices to attract the attention of adolescents. In the teaching of Botany, the use of these resources presents itself as a valuable strategy to develop concepts about plant morphology. The term virtual herbarium is used to designate the availability of digital images of herborized exsiccates via the Internet. Its use can assist in botany classes in high school, since students have the possibility to view images of exsiccates with the convenience of the Internet. The work sought to build a website with images of herborized plant species (exsiccates) and comparative images of plants in vivo, which were used in high school botany classes. Images of herborized and in vivo plants were included on the website, recorded during a floristic survey carried out together with students from a public school in Fortaleza, after which the herbarium was applied to a class at that school. In addition, the site was evaluated using SAM and SMOG, where a satisfactory result was obtained in relation to the objective of the work.